Effect of 5-Aminolevulinic Acid on the Quality and Volatile Metabolites of Korla Fragrant Pear Fruit - SUN Tianyu, WEN Bo, WANG Chunfeng, TIAN Jia, HAO Zhichao, LIN Yan, WEN Yue, ZHANG Feng (Shipin Kexue)
In this study, the effect of applying different concentrations (50, 100, 150 and 200 mg/L) of 5-aminolevulinic acid (5-ALA) at the fruit swelling stage on the quality and volatile metabolites of Korla fragrant pear fruit was examined. The quality of pear fruit with and without calyx was determined at the maturity stage. Meanwhile, comprehensive quality evaluation of pear fruit under 5-ALA treatment was carried out using principal component analysis (PCA), and the optimal 5-ALA concentration for improving the fruit quality was determined. The results showed that exogenous spraying of 150 mg/L 5-ALA had the best effect on improving the quality of fragrant pear fruit. Specifically, compared with the control group, the hardness, stone cell content and titratable acid content of the fruit without calyx decreased by 13.45%, 31.03% and 42.31%, respectively, and the soluble solids content and solid/acid ratio increased by 9.95% and 90.57%, respectively; the hardness, titratable acid content and stone cell content of the fruit with calyx decreased significantly by 12.89%, 48.48% and 30.16%, and the soluble solids content, soluble sugar content and solid/acid ratio increased by 19.33%, 23.51% and 131.63%, respectively. In addition, exogenous spraying of 5-ALA significantly increased the mass fraction of volatile metabolites in both fruits, mainly including terpenoids and esters, enriching their aroma attributes such as woody, fruity, vanilla, fresh, grassy and sweet notes. The differential metabolites between the 5-ALA treatment and control groups were most enriched in the sesquiterpene and triterpenoid biosynthesis pathway. Among them, α-farnesene, 4-[((1E)-1,5-dimethyl-1,4-hexanedi-1-yl]-1-methyl-cyclohexene, δ-cadinene, (E)-1-methyl-4-(6-methylhept-5-en-2-ylidene) cyclohex-1-ene and germacrene B were annotated as key compounds to this pathway, which together endowed Korla fragrant pears with special citrus-like, lavender, lemony, astringent, thyme-like, spicy, earthy, non-medicinal and orange flower-like flavors. In conclusion, it is demonstrated that the exogenous application of 5-ALA significantly improved the quality of Korla fragrant pear fruit, the effect being most pronounced at 5-ALA concentration of 150 mg/L.